PENGGUNAAN SKINCARE DAN PENERAPAN KONSEP BEAUTY 4.0 PADA MEDIA SOSIAL (Studi Netnografi Wanita Pengguna Instagram) - Irwanto, Irwanto; Hariatiningsih, Laurensia Retno (Universitas Bina Sarana Informatika, 2020)
Abstract :This study seeks to uncover the phenomena of waita's use of skincare and the application of the concept of beauty 4.0 in doing and uploading selfies on Instagram social media (IG). The method used is netnography that is by trying to understand deeply the lives of virtual communities from the perspective of the culprit. From the data obtained and collected and processed in relation to the subject and object of the research, the results of the research show that there are stages of the process taken by female Instagram social media users before uploading their selfies. The stages are sequentially the pre-selfie photo phase, selfie photo phase and post selfie photo phase. This research also found that there is an impression management through a message in the form of a selfie that will be uploaded to a social media account.Keywords: selfie, Instagram, skincare, beauty concept 4.0Â